2021
DOI: 10.20886/glm.2021.1.2.123-140
|View full text |Cite
|
Sign up to set email alerts
|

The effect of flooding and light competition on the planting success of degraded tropical peatland

Abstract: Planting was done as a rehabilitation effort at degraded tropical peatland. Understanding the characteristics of the species and environmental conditions that affect plant growth will determine the success of the planting. This study aims to determine the main environmental factors that affect plants in the field so that the right species can be determined. This study used a randomized completely blocked design which was conducted in two stages, namely field testing and verification under controlled condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Knowledge of ecological tolerance species with potential for paludiculture. Sources of data based on literature from: [20,23,10,22,25,12,21,27,18,13,28]. 1.…”
Section: Paludiculture: Native and Non-native Species Adaptive To Pea...mentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of ecological tolerance species with potential for paludiculture. Sources of data based on literature from: [20,23,10,22,25,12,21,27,18,13,28]. 1.…”
Section: Paludiculture: Native and Non-native Species Adaptive To Pea...mentioning
confidence: 99%
“…The high light tolerance of jelutung, balangaran, tumih, terentang, and geronggang species makes these five species as pioneer species in severely degraded peat swamp forests where open areas are little or virtually no tree vegetation remains. The above-average survival rates for the five species are relatively high [7,28]. In addition, balangeran together with other species, namely Galam, is suitable for cultivation in peat swamp forest which is prone to fires because of its fire resistance, as well as because it is resistant to disturbance, although it would be better to plant it in peat swamp forest which is flooded occasionally and is different from that in peat swamp forest Galam prefers moderately/deeply inundation.…”
Section: Familymentioning
confidence: 99%
“…Stands remain after damage as a determining factor and a driving force for success as a source of seeds for natural regeneration [13]. The results of the study at Forest Research of Tumbang Nusa (FRTN) showed that the distance from the seed source/dwelling stand and forest determines the level of species diversity in disturbed areas in peat swamp forest [14].…”
Section: Figure 2 Diversity and Density Of Species After Three Years ...mentioning
confidence: 99%
“…These interventions are in the form of selecting species that are very tolerant to extreme conditions [18], environmental manipulation, and regulation of peat hydrology. Indigenous peat swamp species especially Pioneer species are highly recommended for degraded peatlands [14,15,18,19]. This is due to the native species of peat swamps which have the ability to adapt very quickly to environmental changes, especially inundation that last for a long time [20].…”
Section: Stratum and Speciesmentioning
confidence: 99%
See 1 more Smart Citation